FACULTY OF MUSIC IN EDUCATIONAL SPACE OF A TOWN - Olga V. Tulinova (Высшее образование в России)
The article traces the history and development of the Faculty of Music Education of I.A. Bunin Elets State University, dwells upon the main areas of its activity, shows its role for Elets’ social and cultural life.